Perioperative nursing management of transcatheter edge-to-edge repair (经导管二尖瓣缘对缘修复术围手术期护理) - LIU Yuan (刘苑); LAI Jianqing (赖间清); DING Fei (丁菲); HUANG Huifen (黄惠芬) (中西医结合护理)
This paper summarized the perioperative nursing management of transcatheter edge-to-edge repair. Clinical data of 37 patients with moderate to severe mitral regurgitation were retrospectively analyzed. All patients were transferred to the CCU after transcatheter intervention under general anesthesia. Difficulties and key points of perioperative nursing were fluid management, postoperative rehabilitation and pain control. Based on the fine management model, a goal-directed fluid management plan assisted with the impedance gardiography was established. The comprehensive interventions including enhanced recovery after surgery, respiratory exercise, pain control, catheter maintenance and standard health education before discharge were carried out to relieve symptoms of heart failure, improve self-care ability and quality of life of patients after transcatheter edge-to-edge repair. (本文总结经导管二尖瓣缘对缘修复术围手术期护理要点。37例患者均为二尖瓣中重度反流, 全身麻醉术后由导管室转入冠心病监护病房监护。经导管二尖瓣缘对缘修复术围手术期护理难点主要有容量管理、术后康复、疼痛管理等。因此, 在常规精细化护理基础上, 建立无创心排联合目标导向容量管理, 执行术后快速康复及呼吸肌锻炼, 以及针对性疼痛管理、导管护理和规范化的出院指导。37例患者术后心力衰竭症状明显改善, 自理能力及生活质量得到明显改善。)